Clothianidin and Thiacloprid Mixture Administration Induces Degenerative Damage in the Dentate Gyrus and Alteration in Short-Term Memory in Rats - Alejandra Mora-Gutiérrez; Jorge Guevara; Carmen Rubio; Minerva Calvillo-Velasco; Daniela Silva-Adaya; Socorro Retana-Márquez; Blanca Espinosa; Carmen Martínez-Valenzuela; Moisés Rubio-Osornio (Journal of Toxicology)
Neonicotinoids are pesticides that act as agonists of nicotinic receptors for acetylcholine in insects’ central nervous system (CNS). Chronic exposure to neonicotinoids in humans is related to autism, memory loss, and finger tremor. In this article, we evaluate the effect of subchronic oral administration of two neonicotinoids in the same mixture: clothianidin and thiacloprid. Decreasing doses of both pesticides were administered to rats starting from the lethal dose 50 (LD50) reported by the manufacturer. Our results indicate that the administration of three doses of decreasing amounts of LD50 (5/10, 4/10, and 3/10 LD50) resulted in 100% death in all cases. Ten administration times of 2/10 LD50 of the mixture caused only 20% of death cases after twenty-seven days, which was determined as a subchronic administration scheme. The animals administered 2/10 LD50 showed behavioral alterations after the first and second administration. Electrographic studies showed abnormal discharge patterns in the CNS. 72 h after the tenth dose, learning and memory tests were performed in the Morris water maze. Our results revealed significant decreases in permanence at the quadrant and the number of crosses (P=0.0447, P=0.0193, respectively), which represent alterations in the short-term memory test, but there were no significant changes in a long-term memory test. Likewise, the brains of these animals showed tissue architecture loss, nucleosomal retraction, and a significant increase in the pycnosis of the granular neurons of the dentate gyrus analyzed at 72 h after the last dose (P=0.0125). Toxic effects and cognitive deterioration that have been found in communities living near contaminated areas are probably related to the agricultural use of neonicotinoids.